Proceedings of the Events and Stories in the News Workshop 2017
DOI: 10.18653/v1/w17-2705
|View full text |Cite
|
Sign up to set email alerts
|

Tracing armed conflicts with diachronic word embedding models

Abstract: Recent studies have shown that word embedding models can be used to trace timerelated (diachronic) semantic shifts for particular words. In this paper, we evaluate some of these approaches on the new task of predicting the dynamics of global armed conflicts on a year-to-year basis, using a dataset from the field of conflict research as the gold standard and the Gigaword news corpus as the training data. The results show that much work still remains in extracting 'cultural' semantic shifts from diachronic word … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 8 publications
0
45
0
Order By: Relevance
“…These tasks are critical challenges that are relevant to a range of NLP fields, including the study of historical semantic change. The successful outcome of semantic change detection is relevant to any diachronic textual analysis, including machine translation or normalization of historical texts (Tjong Kim Sang et al, 2017), the detection of cultural semantic shifts (Kutuzov et al, 2017) or applications in digital humanities (Tahmasebi and Risse, 2017a). However, currently, the best-performing models (Hamilton et al, 2016b;Kulkarni et al, 2015;Schlechtweg et al, 2019) require a complex alignment procedure and have been shown to suffer from biases (Dubossarsky et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These tasks are critical challenges that are relevant to a range of NLP fields, including the study of historical semantic change. The successful outcome of semantic change detection is relevant to any diachronic textual analysis, including machine translation or normalization of historical texts (Tjong Kim Sang et al, 2017), the detection of cultural semantic shifts (Kutuzov et al, 2017) or applications in digital humanities (Tahmasebi and Risse, 2017a). However, currently, the best-performing models (Hamilton et al, 2016b;Kulkarni et al, 2015;Schlechtweg et al, 2019) require a complex alignment procedure and have been shown to suffer from biases (Dubossarsky et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Scalable ground census using natural language processing also works well when a curated target-specific learning [16]. However, such approaches do not integrate the growing data collection (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It encodes conflicts, where at least one party is the government of a state. The Armed Conflict Dataset is widely used in statistical and macro-level conflict research; however, it was adapted and introduced to the NLP field only recently, starting with (Kutuzov et al, 2017). Whereas that work was focused on detecting the onset/endpoint of armed conflicts, the current paper further extends on this by using the dataset to evaluate the detection of changes in the semantic relation holding between participants of armed conflicts and their locations.…”
Section: Gold Standard Data On Armed Conflictsmentioning
confidence: 99%